Major Burns After Lightning Strikes at Field: Case Report - Ulfa Elfiah; Wahyu Rachmadi Akbar (Journal of Agromedicine and Medical Sciences, 2022)
Lightning injuries can cause multi-organ damage such as burns, ear damage, and nervous system damage. The type of Burns in this trauma consists of linear or flash burns, punctate burns, thermal injuries, Lichtenburg figures, and combination wounds which are generally superficial and heal faster. Lightning strikes also cause ear damage in the form of perforation of the tympanic membrane, bleeding, and micro fractures in the cochlea. The sequelae in lightning injury survivors consist of permanent brain injury, chronic pain syndrome, peripheral neuropathy, and blindness. This case is a man, 20 years old, working as a farmer, referred to the hospital because he was struck by lightning while working in the middle of the rice fields during heavy rain. There were complaints of pain, heat throughout the body, and decreased hearing in both ears in the anamnesis. Physical examination showed a general condition within normal limits. Local status examination found burns as large as 31.5% of the body area, with 2a degree burns (partial thickness) on the chest, back, upper and lower limbs. Examination of the outer and middle ear revealed no abnormalities. The principle of the treatment refers to the electric burns treatment with initial therapy in fluid resuscitation, evaluation of ECG, adequate analgesia, and wound care. The advanced phase of the treatment focuses on treating the burns and evaluating the hearing loss. Adequate care for nine days showed that the wound was epithelialized by 60% of the total wound area and without any other complaints. This case is essential to be studied considering that Indonesia's natural conditions allow for lightning strikes, especially during the rainy season, so lightning is a threat to farmers as a part of the agro-industrial community. Keywords: Lightning injuries, burns, agroindustrial